PENGARUH PENAMBAHAN ABU VULKANIK GUNUNG KELUD TERHADAP KUAT TEKAN BETON - Sadham Panjang Yuswanto, Pramudiyanto (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2015)
ABSTRACTThis study aims to determine the chemical content Volcanic Ash Kelud and determinethe effect of volcanic ash that has burned at a temperature of 600ºC for concrete compressivestrength. Testing will be done on the physical properties and chemical composition of theVolcanic Ash content Kelud using Atomic Absorption Spectrometry (AAS) and Gravimetryinclude the content of Al2O3, Fe2O3, SiO2, H2O and LO1. This test refers to ASTM 618-03 andSNI 15-0302-2004. Further testing concrete compressive strength with three cylindrical concretespecimen with a diameter of 15 cm and a height of 30 cm to 28 days on each variant. Theaddition of volcanic ash Kelud varied with dose of 0%, 5%, 10%, 15% and 20% of the weight ofcement needed. Data were analyzed with descriptive-quantitative method to determine thefeasibility of volcanic ash in concrete production based on the requirements of new chemicalelements Pozolan nature. The results showed that of the test sample composition chemicalconstituents Volcanic Ash Kelud from Pringwulung village, Depok, Sleman qualify as naturalPozolan. The greater the increase percentage of volcanic ash on the weight of the cement, thecompressive strength of concrete produced increasingly large, the compressive strength ofconcrete against any variation on the addition of volcanic ash Kelud 0%, 5%, 10%, 15% and20% obtained compressive strength average amounted to 34.295 Mpa, 36.731 MPa, 41.881MPa, 42.767 MPa and 46.947 MPa. Where the maximum compressive strength of the concreteobtained with the addition of volcanic ash of 20% and a minimum compressive strength of theconcrete obtained with the addition of volcanic ash at 0% (No Addition).Keywords: Chemical Ingredients, Concrete Compressive Strength, Volcanic Ash Kelud